In Situ Fabrication of 3D Octahedral g‐C3N4/BiFeWOx Double‐Heterojunction for Highly Selective CO2 Photoreduction to CO Under Visible Light. Issue 20 (3rd September 2018) - Wang, Yanan; Zeng, Yiqing; Wan, Shipeng; Cai, Wei; Song, Fujiao; Zhang, Shule; Zhong, Qin
Abstract: A series of g‐C3 N4 /BiFeWO x composites (GN‐x/BFW) with double‐heterojunction composites as photocatalysts for efficient and stable CO2 photoreduction had been rationally designed and synthesized by the facile in situ hydrothermal method. In situ growing BFW on g‐C3 N4 sheets achieved that the g‐C3 N4 was embedded in the inner of BFW as well as wrapped on the surfaces of BFW. The obtained heterojunction composites greatly inhibited the recommendation of photogenerated electron/hole pairs and enhanced the light respond on the visible light due to the tight chemically bonded interface interaction. Benefiting from the unique structure, the optimized GN‐5.0 %/BFW heterostructure catalyst showed a higher performance of photoreduction CO2 to CO (43 μmol h −1 g −1 ) than that of pure BFW (5.2 μmol h −1 g −1 ) and g‐C3 N4 (8.9 μmol h −1 g −1 ) under visible light irradiation at 10 °C. Besides, the GN‐x/BFW composites exhibited outstanding recycling photostability and structural stability. A possible Z‐scheme mechanism was proposed according to the staggered band potentials between g‐C3 N4 and BFW and ESR results. Similarly, this facile synthetic method could be employed to fabricate other composites to accelerate the photocatalytic performance. Abstract : Double up ! A series of g‐C3 N4 /BiFeWO x composites (GN‐x/BFW) with double‐heterojunction as photocatalysts for efficient and stable CO2 photoreduction. The composites exhibited outstanding recycling photostability and structural stability.